Short Communication: The Occurance of Coin Green Seaweeds, at Lhok Bubon Coast, Samatiga, West Aceh: Komunikasi Singkat: Keberadaan Alga Hijau Koin, di Pesisir Lhok Bubon, Samatiga, Aceh Barat - Lisdayanti, Eka; Ayu, Inna Puspa; Asriani, Nenni; Yuliati, Yuliati; Najmi, Nurul; Darmarini, Ananingtyas S (Department of Aquatic Resources Management, Faculty of Fisheries and Marine Science, IPB University, 2024)
This study aims to report the diversity of the Halimeda genus on the West Aceh coast. Data was collected in the Lhok Bubon Coastal intertidal area, Samatiga, West Aceh Aceh Province. Macroalgae samples were collected using the cruising method along the beach with a depth of 1-2 m at low tide. The Halimeda genus found four species, namely Halimeda macroloba, Halimeda macrophysa, Halimeda incrassata, and Halimeda simulans. Halimeda macroloba was found to have a whitish-green talus. Halimeda macrophysa samples have irregular talus branches. Description Halimeda incrassata at the study site is light green, and the holdfast is attached to the sandy substrate to form large sediment clumps. Halimeda simulans were found to be linked to sand, which tends to have a finer texture. The results of this report provide information that Lhok Bubon Beach, West Aceh, has macroalgae potential that needs further study.